2016
DOI: 10.1108/medar-08-2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Implementing basic e-learning tools into an undergraduate taxation curriculum

Abstract: Purpose -Educators in the accounting discipline are faced with the challenge of finding innovative ways to accommodate the flexible learning styles of Millennial students, using "in classroom/contact time" effectively and decreasing transactional distance between students and educators in large classes. In an attempt to address these challenges, this paper aims to describe the implementation of basic e-learning tools (podcasts, vodcasts and voice-over-PowerPoint) as supplementary and substitutional tools in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Accounting and Information Systems relates to studies on the interface between accounting, information systems and technology. Studies in this category focused on audit information technology (Abou‐El‐Sood et al ., ), accounting information systems (Gullberg, ), information technology in an educational setting (van Oordt and Mulder, ), and information technology innovation (Nath et al ., ).…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…Accounting and Information Systems relates to studies on the interface between accounting, information systems and technology. Studies in this category focused on audit information technology (Abou‐El‐Sood et al ., ), accounting information systems (Gullberg, ), information technology in an educational setting (van Oordt and Mulder, ), and information technology innovation (Nath et al ., ).…”
Section: Analyses Of Recent Accounting Publicationsmentioning
confidence: 99%
“…Transactional distance has been described as the cognitive and physiological space between the educator and the learner where possible misunderstandings between educator inputs and the learners' comprehension may occur (Moore 1993). Initiatives aimed at reducing transactional distance, including blended and distributive learning strategies, claim to positively impact the motivation to learn and to increase learner success (Oliver & Trigwell, as cited in Prinsloo & Van Rooyen 2007;Van Oordt & Mulder 2016).…”
Section: Bridging Transactional Distance Through Blended Learningmentioning
confidence: 99%
“…Visser 1998;Song & Keller 2001). Prior research has also established that the use of educational technology personalises learning by giving a voice or putting a face to the learning experience through the creation of a transactional (virtual) presence, and thereby decreasing transactional distance (Lee, Tan & Goh 2004;Van Oordt & Mulder 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Viviers, Fouché and Reitsma (2016) evaluate the usefulness of an educational game to develop soft skills. Van Oordt and Mulder (2016) describe the consequences of implementing basic e-learning tools in an undergraduate taxation curriculum. Kirstein and Kunz (2015) report on the development and implementation of two student-centred approaches, suggesting active student participation in large classes are possible and develops professional skills.…”
Section: Accounting Education (Ed)mentioning
confidence: 99%
“…For educators, studies have suggested the use of technology and social media as beneficial for student learning (Stainbank & Gurr 2016, van Oordt & Mulder 2016 and implementation of innovative and student-focused teaching styles (Kirstein & Kunz 2015, Viviers et al 2016.…”
Section: Accounting Education (Ed)mentioning
confidence: 99%